â€œDAKOCANâ€ GAME ASYIK UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PENCATATAN AKUNTANSI PERUSAHAAN JASA - Agusnila, Triawati (Dinamika Pendidikan, 2014)
The learning objectives will be achieved maximally if the teacher can create the comfortable situation for students in the learning process. Therefore, it needs a new alternative way to optimize the learning by applying an accounting game method by using Dakocan media. Dakocan can help facilitating the learning process in the classroom to improve studentsâ€™ activeness and studentsâ€™ learning outcomes. The purpose of this study was to determine whether Dakocan can improve the studentsâ€™ activeness and learning outcomes on Service Company Accounting records. It was a Classroom Action Research conducted in two cycles. The data were collected by observation, interview, documentation, questionnaires, and test. Then, the data were analyzed by percentage analysis and qualitative descriptive analysis. The studentsâ€™ activeness increased up to 74.08% on the first cycle which it was only 54.05% on the initial observation. The learning completeness (students who achieve mastery learning) was 26 students or 72.22%, meanwhile the average score of daily tests was 78.08%. Then, studentsâ€™ activeness rose up to 87.35% on the second cycle with the learning completeness was 33 students or 91.67%, and the average score of daily tests was 82.89%.Â